2005
DOI: 10.1021/np0401819
|View full text |Cite
|
Sign up to set email alerts
|

Homoflavonoids from Ophioglossum petiolatum

Abstract: Six homoflavonoids, ophioglonin (1), ophioglonin 7-O-beta-D-glucopyranoside (2), ophioglonol (3), ophioglonol prenyl ether (4), ophioglonol 4'-O-beta-D-glucopyranoside (5), and isoophioglonin 7-O-beta-D-glucopyranoside (6), together with five known compounds, quercetin, luteolin, kaempferol, 3,5,7,3',4'-pentahydroxy-8-prenylflavone, and quercetin 3-O-methyl ether, were isolated from Ophioglossum petiolatum. Their structures were elucidated by analysis of spectroscopic data and chemical evidence. Compounds 1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 6 publications
2
28
0
Order By: Relevance
“…The aglycone of compound 5 was thus determined as ophioglonol. 1 Hydrolysis of 5 afforded ophioglonol as the aglycone and D-glucose as the sugar, confirming the above conclusion. The 1 H and 13 C NMR data of the glucosyl moieties of 5 and 1 are identical (Tables 1, 2).…”
supporting
confidence: 66%
“…The aglycone of compound 5 was thus determined as ophioglonol. 1 Hydrolysis of 5 afforded ophioglonol as the aglycone and D-glucose as the sugar, confirming the above conclusion. The 1 H and 13 C NMR data of the glucosyl moieties of 5 and 1 are identical (Tables 1, 2).…”
supporting
confidence: 66%
“…In addition, an Obearing CH 2 group appeared at d(H) 5.33 (s, 2 H) and d(C) 63.7 (C(11)). These NMR data indicated that compound 1 had a homoflavone skeleton [9] .88 were assigned to C(4') and C(3'), respectively, by the HMBCs HÀC(6')/C(2'), C(2), and C(4'), and HÀC(5')/C(6'), C(3'), and C(4'). The other MeO groups at d(H) 4.10, 4.03, 3.95, and 3.95 showed three-bond HMBCs with C-atoms at d(C) 151.0 (C(5)), 137.8 (C(8)), 143.8 (C(6)), and 148.6 (C (7)), respectively.…”
mentioning
confidence: 95%
“…Their ability to inhibit viral RNA translation activities against several plant viruses have been described [49]. Quercetin 3-O-methyl ether and ophioglonin obtained from plants belonging to Ophioglossaceae genus have shown slight activity against HBV [50]. Since 1995 when antiviral activities against enveloped viruses were discovered in extracts of Houttuynia cordata [51], such as influenza, HIV, herpes, SARS and also in enteroviruses [51][52][53][54], 40 compounds have been isolated from the whole plant [55].…”
Section: Resultsmentioning
confidence: 99%
“…In HepG2, none of the 4 extracts with ability to inhibit cell growth (Coptis chinensis, Epimedium brevicornum, Equisetum hiemale and Senecio scandens), were found to induce acute cell toxicity when they were incubated with the IC 50 of the extracts for 6 h ( Figure 2). In SK-Hep1, among the 10 extracts with antitumor effect 7 did not induce acute toxicity (Arctium lappa, Cassia tora, Centipeda minima, Chrysanthemum indicum, Coptis chinensis, Phellodendron chinense and Rheum palmatum), whereas Dysosma versipellis was especially active by lowering the cell viability in comparison to the control to 40% (Figure 3).…”
Section: Resultsmentioning
confidence: 99%